Content, Exposure, and Effects of Public Discourses about Marijuana: A Systematic Review. Issue 12 (2nd December 2018) - Park, Sung-Yeon; Holody, KYLE J.
Abstract : This review presents a comprehensive picture of research studies about marijuana-related content in news, social media, and advertisements. Studies that examined the extent of people's exposure to the messages and its effects were also included. A total of 27 peer-reviewed journal articles and one thesis were located, of which 16 analyzed the content, four contained information about people's exposure to the messages, and ten examined the effects. Over time, news coverage shifted from negative to slightly positive toward marijuana use. Social media and advertisements were overwhelmingly favorable toward marijuana use and legalization by claiming social, romantic, and health benefits of marijuana use while completely downplaying risks. A majority of social media accounts were also run by advocacy groups and industry interests, rather than individuals who were simply sharing opinions or experiences. Furthermore, absence of health authorities among the highly popular social media accounts about marijuana was notable. The news, social media, and advertising messages about marijuana were widely used by the members of public, which in turn generated some demonstrable effects on the audience's marijuana-related perceptions and behaviors. The public and policymakers need to become aware of this information environment for potential marijuana users and take more proactive measures to protect vulnerable populations.